STUDI PERILAKU KONSUMEN: FAKTOR INTERNAL DAN TEKANAN SOSIAL TERHADAP MINAT BELI MEREK GLOBAL SENSITIF - Mouren Ghina Deswita; Nurist Surayya Ulfa (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
This research investigates the impact of consumer resentment, brand image perception, social influence, and consumer attitude on the willingness to buy boycott-targeted global brands within Indonesia's food and beverage sector. The analysis captures the post-boycott cool-down period, characterized by declining public emotional intensity alongside unrecovered purchasing levels. Utilizing an online survey of 200 Indonesian Generation Z respondents, data were processed via multiple linear regression using SPSS. Simultaneous testing confirms that all four determinants significantly dictate buying propensity. Individually, however, only social influence exerts a significant effect. These insights demonstrate that interpersonal pressure from the immediate environment serves as the primary driver suppressing consumer buying willingness toward brands linked to international humanitarian crises.